67. Distance Education in China and India: Collectivism and Connectivism - Carter, Deborah Joy (International Review of Research in Open and Distributed Learning, 2009)
In the last decade, China and India have seen large increases in their literacy and graduation rates and an increasing emphasis on distance education and training initiatives. They are examples of nations in which economic and technological initiatives have been aligned in order to produce outcomes that ensure the population will thrive in the 21st century. However, no country can simply equip its distance education system with updated technologies and expect to be fully prepared for 21st century economic challenges. This report outlines the consonances and dissonances of distance education (DE) in China and India and the policy alignments required for its stable development.